2018
DOI: 10.29392//001c.11927
|View full text |Cite
|
Sign up to set email alerts
|

Supporting strong families and capable communities through cross-national research

Abstract: Back Background ground Mental and behavioral ill-health are growing global problems and while there are promising evidence-based approaches aimed at reducing their impact, availability of services varies greatly, not only across nations, but also between urban, regional, and remote locations. Rural areas face accessibility and acceptability challenges related to mental health services that are similar to barriers experienced in developing countries. Initiatives to address mental health challenges in under-serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The effectiveness of telemental health has national and global implications to improve the mental health of individuals and families (Bischoff et al, 2017; Taylor et al, 2018). More research is needed to identify best practice strategies and the unique characteristics of this treatment modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of telemental health has national and global implications to improve the mental health of individuals and families (Bischoff et al, 2017; Taylor et al, 2018). More research is needed to identify best practice strategies and the unique characteristics of this treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, rural areas are prime destinations for telemental health because of the high level of need, remote locations, lack of access to mental health‐care providers, and opportunities for addressing stigma‐related challenges (Bischoff, Springer & Taylor, 2017; Taylor et al, 2018). However, we have found that telemental health is an appropriate treatment modality for other circumstances where there are barriers to meeting with clients face‐to‐face.…”
mentioning
confidence: 99%